The Urgency of Redefinition of Offense Formulation of Corruption in The Law on The Eradication of Corruption - Al-Fatih, Sholahuddin (Law Research Review Quarterly, 2021)
This research aims to analyse corruption law in Indonesia, especially in the form of offense formulation of corruption in the law on the eradication of corruption. This study used mixed legal method, namely descriptive qualitative method and normative juridical method. This research found that corruption in Indonesia still doing as bussiness as usual. Moreover, in the offense formulation of corruption eradication, there are quite several ambiguous and multi-interpretative norms, that can be interpreted widely by the judge. This condition is very horrible and terrible. In connection with the above conclusions, then there are some things that can be suggested by the authors and are expected to be used as material for consideration for parties related to this research, the government should provide clear and certain offense formulation of corruption and the judges may not interpret the formulation of corruption offenses with the aim of reducing or alleviating the punishment of corruptors.